Germanium Plasmon Enhanced Resonators for Label-Free Terahertz Protein Sensing - Bettenhausen, Maximilian; Roemer, Friedhard; Witzigmann, Bernd; Flesch, Julia; Kurre, Rainer; Korneev, Sergej; Piehler, Jacob; You, Changjiang; Kazmierczak, Marcin; Guha, Subhajit; Capellini, Giovanni; Schroeder, Thomas (Frequenz, 2018)
A Terahertz protein sensing concept based on subwavelength Ge resonators is presented. Ge bowtie resonators, compatible with CMOS fabrication technology, have been designed and characterized with a resonance frequency of 0.5 THz and calculated local intensity enhancement of 10.000. Selective biofunctionalization of Ge resonators on Si wafer was achieved in one step using lipoic acid-HaloTag ligand (LA-HTL) for biofunctionalization and passivation. The results lay the foundation for future investigation of protein tertiary structure and the dynamics of protein hydration shell in response to protein conformation changes.
CRIS-Team Scopus Importer:2021-06-11
Keywords: protein conformation; semiconductor plasmonics; terahertz sensor